Didaktische Implikationen des sprachlichen Grußverhaltens für den Deutschunterricht an Polen - MIODEK, Wacław (Uniwersytet im. Adama Mickiewicza, 1995)
Almost every conversation begins and ends with a formula of greeting and goodbye. Therefore those formulas belong to worth mentioning problems of contemporary sociolinguistics. The present article deals with three aspects of this problem: - the choice of appropriate formula of greeting and goodbye during the communication act in dialogue speech, - the comparison of formulas of greetings and goodbyes presented in German textbooks used in Poland with language reality, and presents methodological clues and examples of exercises which introduce above-mentioned formulas during German language lessons in Poland.